Keabsahan Permohonan Pailit Yang Diajukan Buruh Terhadap Perusahaan Terkait Pemenuhan Haknya (International Forum of Researchers and Lecturers, 2023)
In the second quarter of 2020, Commercial Courts in Indonesia handled 132 bankruptcy cases. In the first semester of 2020, the number of bankruptcy cases handled by the Commercial Court in Indonesia increased to 233 cases, including 43 cases handled by the Central Jakarta Commercial Court. The aim of bankruptcy is basically to provide a solution to the parties if the Debtor stops paying/is unable to pay his debts. Bankruptcy prevents/avoids unfair actions that can harm all parties, namely: avoiding execution by creditors and preventing fraud by the debtor himself. Bankruptcy is a legal institution that has an important function, namely as the realization of two important articles in the Civil Code regarding the debtor's responsibility for the obligations carried out, namely Articles 1131 and 1132. This research aims to determine the validity of the bankruptcy petition submitted by workers to the compliance company. his rights. This research uses normative juridical legal research methods. In this research, what is emphasized is the aspect of law application which is carried out integrally with morality. The research results show that a worker's bankruptcy petition is a petition submitted by workers or labor unions to the commercial court to declare the company where they work bankrupt. A worker's bankruptcy application can be filed if the company does not pay wages, allowances and other rights that should be paid to workers.